2016
DOI: 10.1016/j.redox.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The thioredoxin system in breast cancer cell invasion and migration

Abstract: Metastasis is the most life threatening aspect of breast cancer. It is a multi-step process involving invasion and migration of primary tumor cells with a subsequent colonization of these cells at a secondary location. The aim of the present study was to investigate the role of thioredoxin (Trx1) in the invasion and migration of breast cancer cells and to assess the strength of the association between high levels of Trx1 and thioredoxin reductase (TrxR1) expression with breast cancer patient survival. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 55 publications
4
78
2
1
Order By: Relevance
“…Trx1 overexpression was proved to increase tumour proliferation and invasion15161718. Nevertheless, the roles of TrxR1 in it were not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Trx1 overexpression was proved to increase tumour proliferation and invasion15161718. Nevertheless, the roles of TrxR1 in it were not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Since TrxR is the only enzyme known to catalyze the reduction of Trx-1, it is reasonable that alterations in TrxR activity is likely to regulate some of the activities of Trx-1 [43]. Importantly, high expression of TrxR is associated with a poor cancer prognosis in clinic [16,44]. Our data demonstrated that the enzyme activity of TrxR was dropped though no obvious change in expression was observed following the treatment of DATS.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 65%
“…However, the ability of Cur to increase thioredoxin activity was reduced by half at the MED compared to its hMED, which is not significantly different from the vehicle control (Con). The high induction of thioredoxin activity at the hMED but not at the MED may warrant further study to determine whether it may be related to the resistance of cancer cells to Cur treatment [27].
Fig. 3The effect of food-derived polyphenols on endogenous antioxidant enzymes.
…”
Section: Resultsmentioning
confidence: 99%